Diversity and Abundance of Plants with Flowers and Fruits from October 2001 to September 2002 in Paucarillo Reserve, Northeas- tern Amazon, Peru - Choo, Johanna P.S. (2007)
We recorded the diversity of fl owering and fruiting plants during one year of phenological study at Paucarillo Reserve located in the northeastern part of the Peruvian Amazon (3°41’ S, 72°24’ W). A total of 270 species from 59 families were recorded, of which 57% were represented by only one individual plant. Arecaceae and Rubiaceae were the dominant families in this site.